Metabolism of Oat Leaves during Senescence: VI. CHANGES IN ATP LEVELS - Malik, Nasir S. A. (1980)
The ATP content of 7-day-old Avena sativa leaves during senescence in dark and in light, and after treatment with cytokinins and other reagents, has been determined by the luciferin-luciferase method. Special care was taken to avoid decomposition of the ATP, and a detailed procedure is presented for ATP analysis at the picomole level. Preliminary experiments with several inhibitors of photophosphorylation suggest, though not conclusively, that the delaying effect of light on senescence is mediated by photophosphorylation. The ATP values of the leaves senescing in darkness are found to increase in parallel with the large increase in respiratory rate, and kinetin prevents this increase just as completely as it prevents the respiratory rise. It is concluded that the respiratory increase in senescence cannot be simply due to uncoupling. In light the ATP level also rises, though more slowly, and again kinetin prevents this rise. l-Serine, which promotes dark senescence, does not significantly modify the dark ATP level, but both arginine and kinetin, which antagonize the action of serine on senescence, greatly lower the ATP level below that on serine alone. Cycloheximide has a similar effect, and the combination of cycloheximide and kinetin lowers the ATP level drastically. Fusicoccin, which opens stomata in the dark, correspondingly maintains the ATP at a low level. Thus, in general, a low level of ATP is associated with the prevention of dark senescence, i.e. probably with ATP utilization, and the ATP level at any time may thus be determined more by the rate of utilization than by the efficiency of respiratory coupling.